1985
DOI: 10.1227/00006123-198507000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Subtle Neuropsychological Deficits in Patients with Good Recovery after Closed Head Injury

Abstract: This study demonstrates residual mental deficits in patients who have apparently recovered after closed head injury. Twenty closed head injury patients were compared to 20 normal control subjects matched for age, sex, handedness, education, language, and IQ. All received a series of neuropsychological tests. Discriminant function analysis significantly differentiated the two groups. Correct classification of individuals as having suffered a head injury or not was 85%. The head injury patients did have primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(43 citation statements)
references
References 0 publications
2
41
0
Order By: Relevance
“…The differential interference effect could be due to overload that prohibited rehearsal, or inappropriate resource allocation. Similar results were also reported by Stuss et al (1985), who found that the BrownPetersen interference paradigm was most sensitive to the sequelae of TBI. Our own clinical observations suggested that some severely injured patients did not apply strategies when it would have been appropriate.…”
Section: Deficits Of Capacity and Resource Allocationsupporting
confidence: 89%
See 1 more Smart Citation
“…The differential interference effect could be due to overload that prohibited rehearsal, or inappropriate resource allocation. Similar results were also reported by Stuss et al (1985), who found that the BrownPetersen interference paradigm was most sensitive to the sequelae of TBI. Our own clinical observations suggested that some severely injured patients did not apply strategies when it would have been appropriate.…”
Section: Deficits Of Capacity and Resource Allocationsupporting
confidence: 89%
“…So far, the frontal lobes have been considered as being associated with attentional processes (e.g., Knight, 1984;N~i~it~inen, 1982;Roland, 1982;Stuss et al, 1985), but other authors have stressed the importance of posterior areas, especially the right parietal lobe for attentive behavior (Geschwind, 1982;Heilman et al, 1985;Kornhuber;. Some of the research by Heilman is related to a very specific deficit of attention (i.e., hemi-inattention), which will not be discussed further.…”
Section: Resource Allocationmentioning
confidence: 99%
“…However, studies have documented that a small but clinically significant subgroup of individuals continue to complain of persistent and distressing cognitive, emotional and physical symptoms, in the months and years post injury (Alves et al 1993;Hartlage et al 2001;Powell et al 1996;Ruff and Weyer-Jamora 2009;Stranjalis et al 2008;von Wild 2008). Some of the more frequent areas of cognitive impairment reported by patients with mild TBI can be grouped under the category of "executive" function and include deficits in short term memory, speed of information processing, and attention (Cripe 1987;Gentilini et al 1989;McMillan and Glucksman 1987;Gronwall 1989Gronwall , 1991Leininger et al 1990; Levin et al 1987Levin et al , 1988Levin and Grossman 1978;McMillan 1997;Stuss et al 1985Stuss et al , 1989.…”
Section: Introductionmentioning
confidence: 99%
“…The cognitive constructs working memory (WM) and processing speed are fundamental components to general intellectual functioning in humans (Courtney 2004;Salthouse 1996;Salthouse and Coon 1993) and, critically, both WM and processing speed are highly susceptible to disruption following neurological insult. For example, deficits in WM and processing speed have been documented in TBI (McDowell et al 1997;Stuss et al 1985) multiple sclerosis (Demaree et al 1999;Mostofsky et al 2003;Rao et al 1989a, b), schizophrenia (Cohen et al 1997;Saykin et al 1991Saykin et al , 1994, dementia (Bradley et al 1989;Collette et al 1999; Morris and Baddeley 1988) and normal aging (Salthouse 1992(Salthouse , 1996Salthouse and Coon 1993).…”
Section: Introductionmentioning
confidence: 99%